Analysis of sardine (Sardina pilchardus) and anchovy (Engraulis encrasicholus) catches in the Spanish Mediterranean - Ferrandis E.; Cañizares S.; Abad R.; Báez-Hidalgo M. (Dynamique des populations marines, 1998)
The analysis of landings of two fishing categories, sardine and anchovy, is presented. Within each category there is a target species (Sardina pilchardus and Engraulis encrasicholus, respectively) providing the category name. Monthly landing data (in kg) corresponding to 54 years (1940-1993) have been used from 4 Spanish Mediterranean fishing areas (South Mediterranean, Levant, Tramuntana and Balear), whose geographical distributions are presented in Fig. 1. The contribution (per cent) of each area to the total Spanish Mediterranean landings, and the landing behaviour has been analysed in those areas by using the Spearman correlation by ranges coefficient. Finally, data were treated as time series by estimating the trend with the linear regression model and with the Box and Jenkins methodology, which presents the ARIMA models (Autoregressive Integrate Moving Average) to formulate the series evolution over time. A multiplicative seasonal-non seasonal model is proposed coherent for the evolution of the whole series in the considered period.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)